Ethical management and business theology of modern banjar kiyai analysis of business management of kiyai followers of Guru Sakumpul Martapura and pesantren managers in South Kalimantan - Abdul Sani; Ahmad Syazali; Abdul Hakim; H. Ibnu Arabi (Jurnal Scientia, 2024)
The behavior of Banjar kiyai or ulama in South Kalimantan, especially Pondok Pesantre caregivers, is trending and interesting to explore and study in depth, especially in the sense of modernity of thinking, "glamorous" behavior in a positive sense, such as having productive businesses within the scope of the boarding school with a variety of economic behaviors, such as; travel Hajj and Umrah, owning mineral water businesses, schools and madrasahs, agriculture, animal husbandry and general trade. This main problem is raised about a) How is the reality of the management picture of ethics and business theology of Banjar kiyai followers of Abah Guru Sakumpul? b) How is the main analysis of the driving force of Banjar kiyai followers of Guru Sakumpul in the practice of ethics and business theology in a contemporary manner. This research method uses a qualitative field approach coupled with qualitative literature in the context of documentation of thoughts both from CD lectures, Youtube and other digital recordings. Partial interviews were utilized to track data and at the same time triangulate the analysis of findings. The data object is business ethics and theology in the corridor of modern management rules, including the mindset reconstructed by field data findings. The results of the research findings that the kyai and Banjar Ulama followers of Abah Guru Sakumpul have a variety of businesses with modern management. The meaning of the theology of doing business with the practice of describing the Prophet's business and trying to imitate it is proposed again. The religion of Islam and the Quran is the main business direction of the Banjar kiyai. Allah's Business Management and His Majesty's Business become the main links and characteristics. As a result, the Banjar clerics have successfully done it in their business reactualization.